Implementation of an embedded behavioral health care model in a pediatric rheumatology subspecialty juvenile myositis clinic - Shenoi, Susan; Edison, Suzanne E.; Haynes, Stacey; Patten, Joanna (Frontiers in Psychiatry, 2023)
Youth with chronic medical illness, such as juvenile myositis (JM), require specialized behavioral health care. However, access to such care is challenging due to the youth mental health crisis, which impacts accessibility of mental health services in the community, as well as challenges accessing behavioral health care above and beyond the demands of care related to their JM management. In this paper we describe an embedded behavioral health care model, including the establishment and implementation of such a model, at a pediatric hospital where youth with JM receive medical care in a Center of Excellence (CoE). We describe a unique partnership with a philanthropic organization; the challenges and benefits of delivering care within this model; as well as recommendations for maximizing its effectiveness. Ultimately, we provide an example of a successful embedded behavioral health care program for youth with rare disease, which may be applied to other institutions providing similar care.